Effectiveness of Myofascial Release Technique to Decrease Spasticity in Cerebral Palsy Spastic Hemiplegia - Oktaviana Hariaji, Hapsari; Pritasya Nanda Melip, Dhea; Nurrizky Sutejo, Mianti (STIKES Telogorejo Semarang, 2022)
Background: Spasticity is the most familiar syndromes in cerebral palsy children that is causing some painful spasm. Therefore, some studies suggest that Myofascial Release Technique is able to help the symptomps, in hope it can be able to give less spasticity on cerebral palsy spastic hemiplegia. Research objectives: To find out the effect of Myofascial release technique on spasticity of cerebral palsy spastic hemiplegia children. Methodology:Systematic review of three articles that related with myofascial release technique, cerebral palsy spastic hemiplegia, and spasticity on cerebral palsy spastic. Results:Myofascial release technique can not to gives significant effect to decrease spasticity on cerebral palsy spastic hemiplegia, but itis able to support the other therapy and gives more significant decreasing spasticity along with another therapy. Conclusion:Myofascial release technique is able to gives less spasticity along with other treatment rather than using myofascial release alone. Research contributions: Hapsari Oktaviana Hariaji is the main researcher that selected the topic, wrote the paper, and collected data. Dhea Pritasya Nanda Melip searched, review study document, and collected data. Mianti Nurrizky Sutejo reviewed study document